Using Ciliary Protein PKD-2 Localization in Caenorhabditis Elegans to Study Primary Cilia Form and Function - Grund, Samuel; Przybelski-Lisowski, Tairen; Hamlin, Shelby (My University, 2015)
Current efforts in the lab include categorizing and further characterization of the genes? role in cilia form and function. We hypothesize that candidate factors may affect PKD-2 localization specifically, general transport processes in the cilium, or the structure of cilia or the surrounding support cells.
Color poster with text and photographs.
Keywords: PKD-2 (polycystic kidney syndrome); RNA interference; Cilia; Posters